The relationship between geopolitical risks and housing returns in Türkiye: Evidence from the cross-quantilogram - Engin Bekar (International Econometric Review (IER), 2022)
The aim of the study is to analyze whether geopolitical risks have an effect on housing returns in Türkiye based on the data for the period January 2010 - September 2021. Considering its geography, Türkiye is one of the countries most likely to be exposed to geopolitical risks in the world. For this reason, from the point of view of both domestic and foreign investors investing in housing market, it is important to know whether this situation affects real estate returns, especially in periods when the growth in geopolitical risks is high and very high. For this purpose, in this study, the Cross-Quantilogram method introduced in the paper of Han et al. (2016), which is a robust measure of quantile dependence of two variables, was used. As a result of the analysis, it is seen that median and high-level geopolitical risks do not have an effect on housing prices or housing returns, but very high geopolitical risks have a short-term negative effect on returns. Based on all the findings, it is concluded that the geopolitical risks in Türkiye do not have a significant and permanent effect on the housing market.
Keywords: C01; C13; F50; R31; 330; Geopolitical Risk Historical Index; Housing Price Index; Quantile Dependence; Directional Predictability; Cross-Quantilogram